歯科用エックス線撮影装置の品質管理を目指した実態調査 - 板垣, 恵輔; 四井, 資隆; 古跡, 孝和; 秋山, 広徳; 清水谷, 公成; 蒲生, 祥子 (Shika Hoshasen, 2010)
Objective: In this study, to clarify quality control issues in a dental X-ray unit, we surveyed the uniformity and safety of absorbed doses and exposure time from dental X-ray units, and evaluated image quality of intraoral radiography at Osaka Dental University Hospital.Materials and Methods: Measurements of dose and exposure time were carried out five times and the mean was calculated at twenty-two dental X-ray units in our university hospital using the standard parameters for the mandibular molar region in adults. Intraoral radiography for evaluation of image quality was taken using D-speed films under the standard parameters for the mandibular molar region in adults and E-speed films for pediatric patients. Evaluation of image quality was performed by three oral radiologists.Results: Dose and exposure time differed significantly among units. Image quality of intraoral radiography using D-speed films was not significantly better than that of E-speed films.Conclusion: This study demonstrated that it is necessary to establish a uniform dose and exposure time and to change D-speed films to E-speed films when obtaining intraoral radiography in our hospital.